PERKEMBANGAN PONDOK PESANTREN IQRAâ BARUNG- BARUNG BALANTAI KECAMATAN KOTO TARUSAN KABUPATEN PESISIR SELATAN (1988- 2012) - Sari, Dewi Ratna (Pendidikan Sejarah, 2014)
The background of this research is exist a Muslim boarding school Iqra`, this Muslim boarding school interest by society, though there are many Islamic school and general school which government or private school in sub district Koto XI Tarusan Pesisir Selatan regency. The purpose of this research is describing the background of Muslim boarding school Iqra` was build. This research describes the development of Muslim boarding school since year 1988 â 2012. In this research, the researcher uses the qualitative research, and then the method that use is history method with some step; Heuristic is collect the data with observation and interview, the critical toward variety sources either material or content, then causal explanation is describe or explain in history written with connected the cause effect and interpretation is interpret toward the events. The result of this research is there are some factors which basic of Muslim boarding school was build. However, the principal factor is the desire by some society people for dissemination and development the knowledge and values of education Islam to society so that the society can get the knowledge without went to other country and waste their money. The others factor is the society want the education about Islam religion in their region. So that, the forming of cadres can hold in their region. The development of Muslim boarding school Iqra` begins 1988-2012 get progress, the development guided by Ali Munar Yong Imam Kayo and Buya. H. Azwar Munaf. In conclusion, the result of development of Muslim boarding school Iqra` begin in year 1988-2012 get progress, that the development guided by Ali Munar Yong Imam Kayo and Buya. H. Azwar Munaf. In leadership of Ali Munar Yong Imam Kayo only in Islam Junior High School (Madrasah Tsanawiyah), the curriculum that uses the curriculum of government that is CBSA and curriculum of boarding school. However, in leadership of Buya. H. Azwar Munaf had been builded Islam Senior High School (Madrasah Aliyah), then the quality and quantity is good. The curriculum that uses the KBK and the graduate of Muslim boarding school is always 100% pass in examination and continue to some university in West Sumatera.